Professor Manuel Rodríguez Gómez and the tuberous sclerosis complex paradigm - Otto Jesus Hernandez Fustes; Otto Hernández Cossio; Adriana Hernandez Marques; Olga Judith Hernandez Fustes; Amanda Hernandez Marques (Arquivos de Neuro-Psiquiatria)
ABSTRACT The authors present an historical review of aspects of the life of Professor Manuel R. Gómez, a Spanish neuropediatrician, who graduated in Havana and is known internationally for his work while he was in charge of Pediatric Neurology at the Mayo Clinic in Rochester, USA. His main contribution was related to the tuberous sclerosis complex, demystifying the Vogt triad previously used as a diagnostic criterion, and he was considered the “father of the tuberous sclerosis complex “ in the USA.